Obesity and employment in Ireland: Moving beyond BMI - Irene Mosca (The Economic and Social Research Institute (ESRI), 2012)
I use data from the first wave of the Irish Longitudinal Study on Ageing (TILDA) to investigate the impact of obesity on the labour market status of older Irish individuals. I employ an anthropometric indicator of body composition (waist circumference) along with body mass index. I include a wide array of subjective and objective health indicators in the empirical model. I find that obese women are less likely to be at work. However, both the magnitude and statistical significance of this correlation are sensitive to the definition of obesity. Factors other than socioeconomic characteristics and health are also found to play a role in explaining why obese older women are less likely to be employed. Much weaker evidence is found for men.
Keywords: 330; BMI; waist circumference; employment; older; Ireland